Wpływ kultury organizacji na zarządzanie personelem - Czerska, Małgorzata (The influence of organizational culture into human resources management, 2005)
The paper begins with presentation and classification of organizational culture. We have based on proposition of Schein (four types of culture). Every type of culture needs a different personal strategic (authority - transaction, role - auto selection, support - autonomization, attainment - transformation). Next part of paper describes the differences in HRM implicated by different organizational culture.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 649-657